1992
DOI: 10.1093/nar/20.21.5617
|View full text |Cite
|
Sign up to set email alerts
|

SPO12andSIT4suppress mutations inDBF2, which encodes a cell cycle protein kinase that is periodically expressed

Abstract: To help clarify the role of DBF2, a previously described cell cycle protein kinase, high copy number suppressors of the dbf2 mutation were isolated. Three open reading frames (ORF) have been identified. One ORF encodes a protein which has homology to a human small nuclear riboprotein, while the remaining two are genes which have been identified previously, SIT4 and SPO12. SIT4 is known to have a role in the cell cycle but the nature of the interaction between SIT4 and dbf2 is unclear. SPO12 has until now been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 23 publications
6
54
0
Order By: Relevance
“…Reiser et al the FEAR network such as Spo12 or Cdc5 can, when overproduced, suppress the temperature-sensitive lethality of MEN mutants (Parkes and Johnston, 1992;Jaspersen et al, 1998;Stegmeier et al, 2002). We found that overexpression of SPO12 suppressed the proliferation defect of cdc15-2 mutants as well as of cdc15-2 pbs2⌬ mutants ( Figure 5C).…”
Section: Regulation Of Cdc14 Localization By Stressmentioning
confidence: 51%
“…Reiser et al the FEAR network such as Spo12 or Cdc5 can, when overproduced, suppress the temperature-sensitive lethality of MEN mutants (Parkes and Johnston, 1992;Jaspersen et al, 1998;Stegmeier et al, 2002). We found that overexpression of SPO12 suppressed the proliferation defect of cdc15-2 mutants as well as of cdc15-2 pbs2⌬ mutants ( Figure 5C).…”
Section: Regulation Of Cdc14 Localization By Stressmentioning
confidence: 51%
“…There are a number of genes, encoding regulatory proteins, that, when mutated, cause a cell cycle arrest similar to mob1 mutants. There is an extensive array of genetic interactions linking them together, suggesting that they belong to a common pathway (Pringle and Hartwell, 1981;Wickner et al, 1987;Johnston et al, 1990;Parkes and Johnston, 1992;Kitada et al, 1993;Molero et al, 1993;Spevak et al, 1993;Keng et al, 1994;Shirayama et al, 1994aShirayama et al, , 1994bShirayama et al, , 1996Toyn and Johnston, 1994). We have begun to establish that MOB1 shares genetic interactions with several members of this class of genes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the preliminary events of S phase occur in late mitosis (for example see Cocker et al, 1996). Deletion of SPO12 and SIC1 both lead to a slight protraction of M phase (Donovan et al, 1994;Parkes and Johnston, 1992) and perhaps, in the absence of Pho85, defects occur in the M-G1 transition leading to the observed temperature sensitivity in the double mutants.…”
Section: Discussionmentioning
confidence: 99%
“…We have used Dbf2 as a probe to study the events of late mitosis (Johnston et al, 1990;Parkes and Johnston, 1992;Donovan et al, 1994;Johnston, 1993, 1994). One approach was to isolate dosage suppressors of dbf2 ts alleles, which normally cause arrest in telophase.…”
Section: Introductionmentioning
confidence: 99%